Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Pupuk Organik (P3O) Ngembat Gondang Mojokerto - Fitrotin Jamilah; Yusuf Suharto (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2023)
This study discusses training in making organic fertilizer in Ngebat Gondang Village, Mojokerto, in 2023 using the Participatory Action Research (PAR) method. This training aims to increase the understanding of village communities about organic farming practices and the manufacture of organic fertilizers. PAR methods are used to actively engage communities in research and learning processes, enabling them to play a key stakeholder role in developing solutions that are relevant to their local conditions. The results of this study indicate that PAR methods are effective in increasing community participation in training and helping them adopt agricultural practices organic more effectively. Understanding of the manufacture of organic fertilizers increased significantly, resulting in increased agricultural productivity and reduced use of chemical fertilizers. In addition, close collaboration between village communities, researchers and village government played an important role in the success of this initiative. The results not only create positive changes in farming practices, but also inspire other communities to adopt sustainable practices, creating opportunities for more sustainable agriculture and a healthier environment in the future.